Quaternary Geological Phenomena in Labuhan Area, Pandeglang Regency, Banten Province - Batu, U. Lumban; Poedjoprajitno, S. (Geological Agency, 2012)
DOI:Â 10.17014/ijog.v7i4.148Geological features in Labuhan area were studied from the middle of October to the middle of November 2011 covering seventy days. Surface and subsurface data were obtained from interpretation of landsat images and shallow hand-auger boreholes. The geological features are distinctly associated with active tectonics. The stratigraphy clearly indicates at least three phases of tectonic activities since the Late Miocene until Holocene. Tectonics of phase one occurred in the Late Miocene; phase two took place in the period from Pliocene to Late Pleistocene, while tectonics phase three is ongoing in the Holocene. Volcanic activity has intensified since the Early Pleistocene. The landsat images show an irregular outline of the northern coast line. This penomenon is interpreted to be the result of tectonic uplift. On the other hand, the southern coast is linear in plan which is interpreted to correlate with tectonic subsidence. Furthermore, stratigraphic correlation shows that depositional environment changed vertically due to a local subsidence. The northern researched area is occupied by Pleistocene volcanic eruption centres, whilst the younger ones tend to shift southward. This fact tends to indicate that the subduction zone moved southward slowly.